2006
DOI: 10.1093/aje/kwj145
|View full text |Cite
|
Sign up to set email alerts
|

The Long-term Effect of Insomnia on Work Disability

Abstract: Chronic insomnia is common in the general population. Its effect on functioning and disability is usually attributed to an underlying condition, so the diagnosis of insomnia does not qualify for award of a disability pension in the United States or Europe. The aim of this study was to investigate whether insomnia, defined according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, contributed to long-term work disability. Using a historical cohort design, the authors gathered baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 25 publications
8
118
2
3
Order By: Relevance
“…However, the influence of recovery through sleep at baseline on exhaustion severity at follow-up and the influence of sleep variables on full return to work were weakened when depression was taken into account. In contrast with our findings, prior studies found that sleep problems impeded return to work in the general population, even after adjustment for psychiatric morbidity (22,23). This discrepancy may be due to our small sample size.…”
Section: Poor Recovery Through Sleep and Sleep Problemscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the influence of recovery through sleep at baseline on exhaustion severity at follow-up and the influence of sleep variables on full return to work were weakened when depression was taken into account. In contrast with our findings, prior studies found that sleep problems impeded return to work in the general population, even after adjustment for psychiatric morbidity (22,23). This discrepancy may be due to our small sample size.…”
Section: Poor Recovery Through Sleep and Sleep Problemscontrasting
confidence: 99%
“…In addition, sleep problems are related to long-term sick leave and work disability. In two large-scale epidemiologic studies, sleep problems predicted work disability, even after adjustment for psychiatric and physical morbidity and health-related behavior (22,23). Consequently sleep problems appear to be an independent complicating factor in both symptom improvement and return to work in clinical burnout.…”
Section: Role Of Sleepmentioning
confidence: 99%
“…Åkerstedt et al (17) found that self-reported disturbed sleep and fatigue predict later long-term sickness absence. Similarly, in a prospective study, Sivertsen et al (18) reported that insomnia was a strong predictor of subsequent permanent work disability. In another prospective study in a large sample of 50-60-year old employees, evidence was found that work-related stressors were associated with the development and maintenance of insomnia (19).…”
mentioning
confidence: 89%
“…Workers with insomnia syndrome report reduced productivity, are absent 8.1 h more per 3-month period, [94], and have a greater tendency to show up to work late than do those without insomnia [95]. Insomnia is Epidemiology of Insomnia 19 associated with a reduced likelihood of future professional advancements (e.g., promotion, salary increase) [96][97][98] and increased risk of permanent work disability , even after controlling for baseline exposure to disability and sick leave, sleep duration, and other possible confounders [97][98]. Compared to good sleepers, those with sleep disturbances report more intentions of switching occupations, have reduced job satisfaction and fewer adaptive coping skills, rely more on emotion-oriented coping strategies than problem-solving strategies, and report lower feelings of mastery [99].…”
Section: Long-term Consequences Of Insomniamentioning
confidence: 99%